2020
DOI: 10.1017/s1368980019005238
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception and behaviour related to low-alcohol wine: do people overcompensate?

Abstract: AbstractObjective:Compared with standard wines, low-alcohol wines may have several social and health benefits. Innovative production processes have led to high-quality light wines. It is, however, unclear how consumers perceive and consume these alcohol-reduced wines. The current study aimed to investigate how people evaluate low-alcohol wine (Sauvignon Blanc) and if the reduction in alcohol and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…However, two other studies showed that low alcohol labelling did not increase consumption or intended consumption. In a study by Bucher et al [57], participants consumed equal amounts of wine, whether that be standard wine (12.5% Sauvignon Blanc) or wine with reduced alcohol content (8% Sauvignon Blanc) [57]. These results are in line with the findings of another recent experimental study that concluded that reducing wine alcohol content had neither physiological nor cognitive influence on the quantities consumed [67].…”
Section: Does Low Alcohol Wine Reduce Alcohol Consumption?supporting
confidence: 61%
See 4 more Smart Citations
“…However, two other studies showed that low alcohol labelling did not increase consumption or intended consumption. In a study by Bucher et al [57], participants consumed equal amounts of wine, whether that be standard wine (12.5% Sauvignon Blanc) or wine with reduced alcohol content (8% Sauvignon Blanc) [57]. These results are in line with the findings of another recent experimental study that concluded that reducing wine alcohol content had neither physiological nor cognitive influence on the quantities consumed [67].…”
Section: Does Low Alcohol Wine Reduce Alcohol Consumption?supporting
confidence: 61%
“…In a recent wine study by Bucher et al, participants were randomly assigned to one of three conditions; a low-alcohol (8%) condition, a blinded low-alcohol (8%) condition, or a standard condition Sauvignon Blanc (12.5%). Participants in all three conditions reported similar results for liking of the wine and pleasantness to drink [57]. It should be noted that a further reduction in strength, i.e., <8% may have different results.…”
Section: Tastementioning
confidence: 61%
See 3 more Smart Citations